Quality of Food Products Chicken Crepes - Permatasari, Putery; Al Awwaly, Khothibul Umam; Susilo, Agus (Jurnal Ilmu dan Teknologi Peternakan Tropis, 2022)
Chicken meat is a good source of protein, because it contains complete essential amino acids. Utilization of chicken meat in the manufacture of gluten-free crepes to increase economic value and as a source of protein that can be used as a functional snack for people with gluten intolerance. The purpose of this study was to determine the best quality of gluten-free chicken crepes in terms of organoleptic values and the best treatment using chicken meat and to determine the functional groups of the best treatment crepes. This study used a completely randomized design (CRD) method consisting of 4 treatments and 4 replications, namely treatment P0 the use of chicken meat by 20%, P1 the use of chicken meat by 25%, P2 the use of chicken meat by 30%, P3 the use of chicken meat by 35%. The results showed that the use of chicken meat with different proportions had a very significant effect (p<0.01) on the organoleptic value (texture and color), had a significant effect (p<0.05) on the organoleptic value (aroma and acceptance) and did not. significantly different (p>0.05) on the organoleptic taste. Organoleptic characteristics with a crunchy texture to very crispy, dark yellow to bright yellow, slightly chicken-scented to chicken-scented, slightly savory to savory taste and can be accepted by consumers. The conclusion of the study was that he use of more chicken meat can improve the organoleptic quality (taste and aroma) of gluten-free chicken crepes, but decrease the organoleptic quality (texture, color and acceptance) of gluten-free chicken crepes. The best treatment of gluten-free chicken crepes was P1 with the use of chicken meat by 20%. FTIR absorption band indicates the presence of amide compounds present in chicken crepes, and has 15 kinds of amino acids consisting of 9 essential amino acids and 6 non-essential amino acids and has a saturated fatty acid (SFA) of 2.8%, monounsaturated fatty acids (MUFA) 2.27% and polyunsaturated fatty acids (PUFA) 0.79%.Keywords:  crepes, chicken meat, quality product